PHYTOCHEMICAL PROFILING, FREE-RADICAL SCAVENGING AND ANTI-INFLAMMATORY ACTIVITIES OF MELIOSMA SIMPLICIFOLIA (L.) - PAVITHR, S.; SEKAR, T. (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: In the current research, to determine the stem extract of Meliosma simplicifolia (L.) for total phenol, tannin, total flavonoid, antioxidant activity, anti-inflammatory and identify the phytoconstituents utilizing GC-MS and FT-IR. Methods: The ability of the plant extract to act as hydrogen/electrons donor or scavenger of radicals was determined by in vitro antioxidant assays using 2,2-diphenyl-2-picryl-hydrazyl free radical (DPPH) scavenging, reducing power assay, superoxide radical (O2•) scavenging activity. The anti-inflammatory activity was evaluated using carrageenan and formalin-induced paw edema models using Wistar albino rats. The GC-MS and FT-IR analysis of the methanolic stem extract of M. simplicifolia was revealed the presence of phytochemicals. Results: Quantitative studies of estimated phenol, flavonoid and tannin, as for the methanol extract of stem showed the highest content of phenolic compounds (39.83±3.62GAE mg/100). Antioxidant activities were concluded the estimation M. simplicifolia stem for as followed the studies. In stem the methanol extract showed the highest DPPH scavenging activity (124.3µg/ml). The anti-inflammatory activity has shown in high doses of methanolic extract 250 mg/kg of significant value (p<0.05) inhibition of paw edema, on 6th hour, respectively. The FT-IR analysis has confirmed their characteristic peak values and functional groups. Conclusion: M. simplicifolia has an effective of anti-inflammatory activity and constitutes a potential source for the development of new treatments.